Enhancement of technological innovation capacities in environment friendly approach - Tuan, Nguyen Quang; Xuyen, Nguyen Huu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Technological innovation capacity is one of important factors impacting technological innovation activities of enterprises in general and of technological innovation activities in environment friendly approach in particular. This topic gets attention from many researchers and managers in a target to enhance technological innovation capacities of enterprises and by this way to push enterprises to innovate technologies and to mitigate environment negative impacts from technologies. However, the awareness from enterprises and State policies in this field is not high. This paper is to give answers to the following questions: (i) How to interpret the technological innovation and technological innovations in environment friendly approach?, (ii) How is the actual situation of technological innovation capacities of enterprises in environment friendly approach?, (iii) What should the State authorities do, and in what priority order, to enhance technological innovation capacities of enterprises in environment friendly approach?